2021
DOI: 10.3390/jcm10122660
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis in Liver Transplant Recipients: A Systematic Review

Abstract: Infective Endocarditis (IE) is associated with significant mortality. Interestingly, IE in patients with liver transplantation has not been adequately described. The aim of this review was to systematically review all published cases of IE in liver transplant recipients and describe their epidemiology, microbiology, clinical characteristics, treatment and outcomes. A systematic review of PubMed, Scopus and Cochrane Library (through 2nd January 2021) for studies providing epidemiological, clinical, microbiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Studies relying mostly on case reports and case series specifically involving renal and liver organ recipients, often found Enteroccocus spp. to be an equally common or even more common agent of infective endocarditis than S. aureus [15 ▪ ,16,19]. Tamzali et al [8 ▪ ] in their case–control study, also found enterococci as the most common cause of infective endocarditis in renal transplant recipients.…”
Section: Etiologymentioning
confidence: 95%
See 3 more Smart Citations
“…Studies relying mostly on case reports and case series specifically involving renal and liver organ recipients, often found Enteroccocus spp. to be an equally common or even more common agent of infective endocarditis than S. aureus [15 ▪ ,16,19]. Tamzali et al [8 ▪ ] in their case–control study, also found enterococci as the most common cause of infective endocarditis in renal transplant recipients.…”
Section: Etiologymentioning
confidence: 95%
“…Symptoms of infective endocarditis at presentation in SOT recipients have been characterized mainly through case reports and case series. Fevers seem to be present in 75–100% of patients, alongside acute kidney injury in 40% and embolic phenomena in 38–46% [16,19]. Infection of the left side of the heart, as in the general population, is most common, with the aortic and mitral valve being involved in similar proportion [6 ▪▪ ,8 ▪ ,15 ▪ ].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…GNB-IE represents almost 10% of all episodes of IE in a series of 62 cases of IE in liver transplants [87 ▪ ] and 14.8% of the 117 cases in another study including kidney transplants [88 ▪ ].…”
Section: Introductionmentioning
confidence: 92%